Study of Correlation between Volatility of Stock, Exchange and Gold Coin Markets in Iran with DCC-GARCH Model - Firouz Fallahi; Jafar Hghighat; Naser Sanoubar; Khalil Jahangiri (Faslnāmah-i Pizhūhish/Nāmah-i Iqtisādī, 2014)
Abstract The aim of this paper is to investigate the behavior of stock, exchange and gold coin markets and their correlations structure by using the DCC-GARCH model and the daily data for the period from 23 July 2011 to 22 September 2013 in Iran. Results show that there is a high correlation between returns of Exchange rate and gold coin. But the correlation between returns of stock market index and Exchange rate or gold coin is low. Policy implications on portfolio strategies under DCC model results are also discussed.